Structural Equation Model For Stress Among Employees In Affiliated Colleges - Ramamoorthy R, Dr Ravikumar A (International Journal of Advanced Science and Technology, 2020)
Stress impacts everyone in the workplace. Irrespective of the kind of work a person does his economic back ground or his age no one is immune from stress. It have effect on family well-being and health of an individual. The WHO says that stress is an “Epidemic across Globe”. The United Nation Organization calls the stress resulting from job as “the disease of 20th Century” The frightening reality is that “Immunity is completely absent against stress”, for it can affect anyone. Stress in the workplace, is due to the inter-connected, competitive and profit-driven organizational culture, these features along with “round-the-clock” connectivity through cell phones and computers also add to stress levels. This paper focus on proposing a structural equation model for stress among faculties in affiliated colleges. The categories of stressors considered are On the job stressors, Off the job Stressors and Self-created Stressors.